2018
DOI: 10.1016/j.jfa.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative K-theory for Banach algebras

Abstract: Abstract. Quantitative (or controlled) K-theory for C * -algebras was used by Guoliang Yu in his work on the Novikov conjecture, and later developed more formally by Yu together with Hervé Oyono-Oyono. In this paper, we extend their work by developing a framework of quantitative K-theory for the class of algebras of bounded linear operators on subquotients (i.e., subspaces of quotients) of Lp spaces. We also prove the existence of a controlled Mayer-Vietoris sequence in this framework.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We will follow the notation in [46]. One may refer to [6,29] for more detail about the controlled K-theory for C -algebras and L p -algebras.…”
Section: Obstruction Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…We will follow the notation in [46]. One may refer to [6,29] for more detail about the controlled K-theory for C -algebras and L p -algebras.…”
Section: Obstruction Groupmentioning
confidence: 99%
“…Yeong-Chyuan Chung developed a quantitative K-theory for Banach algebras [6] and applied this theory to compute K-theory of L p crossed products [7]. Chung showed that the L p Baum-Connes conjecture for G with coefficient in C.X / is true if the dynamical system G Õ X has finite dynamical complexity, a property introduced by Guentner-Willett-Yu [17] and obtained a partial answer about p-independence of L p crossed products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ordinary K-theory developed in [1] of Banach algebras is focused on idempotents or invertibles, in comparison, quantitative K-theory studied in [2] for Banach algebras is focused on quasi-idempotents or quasi-invertibles. In this section, we recall some basic definitions and theorems of quantitative K-theory for filtered SQ p algebras from [2].…”
Section: Quantitative K-theory For L P Operator Algebrasmentioning
confidence: 99%
“…Based on their work, Yeong Chyuan Chung later extended the framework of quantitative K-theory to the class of algebras of bounded linear operators on subquotients of L p spaces for p ∈ [1, ∞) (i.e. SQ p algebras) in [2]. Since an L p operator algebra is obviously an SQ p algebra, we can derive a framework of quantitative K-theory for L p operator algebras by applying Chung's work to the L p operator algebras.…”
mentioning
confidence: 99%